Human papillomavirus testing by self-sampling: assessment of accuracy in an unsupervised clinical setting. - Szarewski, A; Cadman, L; Mallett, S; Austin, J; Londesborough, P; Waller, J; Wardle, J; Altman, D; Cuzick, J (2007)
OBJECTIVES: To compare the performance and acceptability of unsupervised self-sampling with clinician sampling for high-risk human papillomavirus (HPV) types for the first time in a UK screening setting. SETTING: Nine hundred and twenty women, from two demographically different centres, attending for routine cervical smear testing. METHODS: Women performed an unsupervised HPV self-test. Immediately afterwards, a doctor or nurse took an HPV test and cervical smear. Women with an abnormality on any test were offered colposcopy. RESULTS: Twenty-one high-grade and 39 low-grade cervical intraepithelial neoplasias (CINs) were detected. The sensitivity for high-grade disease (CIN2+) for the self HPV test was 81% (95% confidence interval [CI] 60-92), clinician HPV test 100% (95% CI 85-100), cytology 81% (95% CI 60-92). The sensitivity of both HPV tests to detect high- and low-grade cervical neoplasia was much higher than that of cytology (self-test 77% [95%CI 65-86], clinician test 80% [95% CI 68-88], cytology 48% [95% CI 36-61]). For both high-grade alone, and high and low grades together, the specificity was significantly higher for cytology (greater than 95%) than either HPV test (between 82% and 87%). The self-test proved highly acceptable to women and they reported that the instructions were easy to understand irrespective of educational level. CONCLUSIONS: Our results suggest that it would be reasonable to offer HPV self-testing to women who are reluctant to attend for cervical smears. This approach should now be directly evaluated among women who have been non-attenders in a cervical screening programme.